The modification of natural rafflesia tourism sites in Ranau, Sabah and its influence on the functional species at those stereotyped habitat - Robert Francis , Peters (2008)

(untitled)
The implementation of nature-based tourism activities at naturally unique sites is expected to contribute to environmental needs while not foregoing socio-economic needs of the area. However, there is increasing evidence that nature-based tourism activities are also threatening natural forested areas. This threat normally comes from the modification of unique sites to suit the perceived market demands. In a case study at Sabah, the modification of natural Rafflesia sites in Ranau for tourism purposes is placing a new pressure at these sites. Three Rafflesia locations with different vegetation in Ranau that is being operated by indigenous communities for tourism, was chosen for a scientific study. The fauna population such as rodents, squirrels, and tree-shrews at these tourism sites were observed and described. The result of this study showed that the function of the species at the different vegetation remained unchanged. However, species abundance had changed in accordance to the kind of modification carried out at these nature–based tourisms sites. This study confirmed that both fauna and flora at the studied sites had changed due to tourism-related modification. Nevertheless, it is difficult to determine the impact of these changes on the survivability of Rafflesia or the sustainability of these tourism sites. Hence, while it is clear that local participation in tourism through Rafflesia-viewing related activities seem promising for the immediate future, long-termed tourism prospect which depends much on the survivability of these flowers, will continue to be uncertain if no effort is placed on the investigation of long-termed habitat stereotyping effect at Rafflesia tourism sites.